ANALISIS MODEL PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN PERBANKAN YANG GO-PUBLIC DI BURSA EFEK INDONESIA (PT. BEI) - Febry Sanur Saputra (Jurnal Ekonomi Pembangunan, 2009)
Purpose of this research is applying of prediction model of company bankruptcy of banking which go-public in Indonesia based on the company financial statements. Model who applied is Model Z-Altman applied to predict company's finance performance. This model applies combination of standard ratios, which are circulating capital ratio, profit ratio arrested, profit ratio before interest and tax, equity market value ratio and sale ratio. In this research applied also financial ratios CAMEL as comparator, with level of health that has been specified Bank Indonesia. Sampling method in this research is method purposive sampling, consisted of eight banking company in Indonesia Stock Exchange/Bursa Efek Indonesia (BEI) and included in catalog 10 banks with the biggest leg asset until end of time line 2008. Result of research indicates that from model Altman and CAMEL leaves for back. Model Altman predicts that all sample bank stays at potential condition gone broke, while CAMEL predicts sample bank to stay at healthy condition.